The institutional of Waqf in Malaysia: Awareness, accountability and transparency towards performance and economic growth. - Ibrahim, Haslindar (Universiti Sains Malaysia, 2014)
Nowadays, waqf has been an important institution for Muslim economic well being. Based on history, waqf has been successfuly practice in the sixteenth-century during the Ottoman empire (Toraman et aI., 2004). Unfortunately, various studies found that there are still an ongoing issue of accountability and transparency of the waqf trustees. As a result, the standard waqf accounting should be enforced to complement the issues. As such, this study attempts to investigate the degree of awareness towards vitality of cash waqf.